Analisis Penentuan Tarif Rawat Inap dan Perhitungan Harga Pokok Pada Klinik Utama Rawat Inap dr. Yati Zarnudji - Ajmi, Dinda Nur; Iriyadi, Iriyadi (Jurnal Ilmiah Akuntansi Kesatuan, 2018)
In general, the establishment of a company is aimed to create profits in order to maintain the business in the long term. The more companies that are established the higher the level of competition. In determining profit, the company's strategy is needed to win the level of competition. Clinic is one of the companies in the service sector, where the determination of his hospitalization rates become one of the company's strategy to determine how profits or profits obtained and expected during a certain period. Therefore, companies need to calculate the cost of goods accurately as a basis for information in decision making, profit planning, job evaluation and cost efficiency monitoring. The purpose of this study is to find out how the rates are determined associated with calculating the cost of inpatient services in 2017. The author conducted research at the Main Clinic Inpatient dr. Yati Zarnudji is located on Jl. Pabuaran Indah No. 31 Kel. Pabuaran Mekar Kec. Cibinong Kab. Bogor 16916. This study uses qualitative descriptive analysis method. This qualitative descriptive analysis method showed calculating the cost of inpatient care services through a financial data and information gathered from the documentation, which is then performed according to the method of data processing in a literature review. The results showed that the calculation of the cost of services based on the analysis results obtained in the VIP class is Rp. 1.211.742, Main class is Rp. 969.394, Primary class is Rp. 848.219, class II A is Rp. 424.110, class II B is Rp. 545.284, and class III Rp. 363.523. As for the rates imposed by the Main Inpatient Clinic Dr. Yati Zarnudji that VIP class is Rp. 500,000-, Main class is Rp. 400,000-, Primary class is Rp. 350,000-, class II A is Rp. 175,000-, class II B is Rp. 225,000-, and class III is Rp. 150,000-,. Therefore, the efficiency costs incurred is required by considering the factors in determining rates of hospitalization such as people's purchasing power, and the rates applied in hospitals or other clinics. Keywords: inpatient rates, cost of good sold, hospital